2018
DOI: 10.1002/jpln.201700528
|View full text |Cite
|
Sign up to set email alerts
|

Effects of biochar application on soil potassium dynamics and crop uptake

Abstract: Biochar has been suggested as a possible means for enhancing soil fertility, including soil potassium (K). However, understanding of the effects of biochar on soil K dynamics remains limited. In this study, a pot trial was conducted to investigate the influence of biochar application (0, 5, 10, and 25 g kg−1 soil) on soil K dynamics and crop K uptake under a winter wheat–maize rotation in two types of soil (an Alfisol, which contained a high initial available K and an Entisol, which contained a high abundance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
45
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(51 citation statements)
references
References 34 publications
4
45
2
Order By: Relevance
“…Previous research indicated that biochar increases the amount of exchangeable K because of increasing the soil CEC [35,45]. However, in this study, the amount of exchangeable K was reduced (except for RHB-1), presumably as the biochar increased the uptake of K by the plants [43,46].…”
Section: Exchangeable Kcontrasting
confidence: 63%
See 1 more Smart Citation
“…Previous research indicated that biochar increases the amount of exchangeable K because of increasing the soil CEC [35,45]. However, in this study, the amount of exchangeable K was reduced (except for RHB-1), presumably as the biochar increased the uptake of K by the plants [43,46].…”
Section: Exchangeable Kcontrasting
confidence: 63%
“…A number of studies have indicated that mixing biochar with soil can effectively improve the soil's physical and chemical properties [30][31][32][33], with biochar also improving the drainage, aeration, and water retention in clay [34], sandy [35,36], hard and compact [17], acidic [28,37], alkaline [38,39], and saline soils [4,[40][41][42]. Biochar can increase the nutrient uptake ability of plant roots [43][44][45][46].…”
Section: Introductionmentioning
confidence: 99%
“…Similar higher SOM values were reported by Sukartono et al (2011) when coconut shell biochar was added with manure to soil. Increased potassium availability in soil is another common effect of biochar reported by many others (Wang et al 2018).…”
Section: Biochar-soil Incubation Experimentsmentioning
confidence: 72%
“…Microbiome studies from three different European sites (UK, France and Italy) after application of same biochar indicated a shift towards copiotrophic ecology and increased mobility of ammonium and phosphates and, therefore, an increased availability of these two nutrients to crops (Jenkins et al 2016). Biochar application not only increased the potassium availability in soils directly, but also enhanced the growth of potassium solubilizing bacteria which could then solubilize K-containing minerals in soils with high K contents (Wang et al 2018).…”
Section: Treatmentsmentioning
confidence: 99%
“…It has been reported that a high quantity of K in BCs could enhance the bioavailable pool of K in the soil [50]. Application of BCs might also improve soil mineral K release by enhancing the activity of K-dissolving bacteria and facilitating K uptake by crops [51]. Syuhada et al [52] found that the K content in corn tissue was significantly higher but its tissue content of N, Ca, and Mg was lower in BC-amended plants than that of the control.…”
Section: Resultsmentioning
confidence: 99%